Influence of political and medical leaders on parental perception of vaccination: a cross-sectional survey in Australia - Elissa J Zhang; Abrar Ahmad Chughtai; Anita Heywood; Chandini Raina MacIntyre (BMJ Open)
Objectives The aim of this survey was to investigate parental vaccination attitudes and responses to vaccine-related media messages from political and medical leaders.Design This was a cross-sectional study using a semiquantitative questionnaire. Data were analysed using descriptive statistics, X2 tests and logistic regression.Setting Data were collected from a web-based questionnaire distributed in Australia by a market research company in May of 2017.Participants 411 participants with at least one child under 5 were included in this study. The sample was designed to be representative of Australia in terms of gender and state of residence.Primary and secondary outcome measures The primary outcome measures were parental attitudes towards childhood immunisation before and after viewing vaccine-related messages from political and medical leaders, including Donald Trump (USA), Pauline Hanson (Australia) and Michael Gannon (Australia). Parents were classified as having ‘susceptible’ (not fixed) or ‘fixed’ (positive or negative) views towards vaccination based on a series of questions.Results Parents with fixed vaccination views constituted 23.8% (n=98) of the total sample; 21.7% (n=89) were pro-vaccination and 2.2% (n=9) were anti-vaccination. The remaining 76.2% of participants were classified as having susceptible views towards vaccination. Susceptible parents were more likely to report a change in their willingness to vaccinate after watching vaccine-related messages compared with fixed-view parents, regardless of whether the messaging was positive or negative (Trump OR 2.54, 95% CI (1.29 to 5.00); Hanson OR 2.64, 95% CI (1.26 to 5.52); Gannon OR 2.64, 95% CI (1.26 to 5.52)). Susceptible parents were more likely than fixed-view parents to report increased vaccine hesitancy after viewing negative vaccine messages (Trump OR 2.14, 95% CI (1.11 to 4.14), Hanson OR 2.34, 95% CI (1.21 to 4.50)).Conclusions The findings suggest that most parents including the vaccinating majorty are susceptible to vaccine messaging from political and medical leaders. Categorising parents as ‘fixed-view’ or ‘susceptible’ can be a useful strategy for designing and implementing future vaccine promotion interventions.